Beyond sinology : Chinese writing and the scripts of culture - Bachner, Andrea (Global Chinese culture., 2014)
New communication and information technologies remain challenging for the Chinese script, which, unlike alphabetic or other phonetic scripts, relies on multiple signifying principles. In recent decades, this multiplicity has generated a rich corpus of reflection and experimentation in literature, film, visual and performance art, and design and architecture, both within China and different parts of the West. Approaching this history from alternative theoretical perspectives, this volume pinpoints the phenomena binding languages, scripts, and medial expressions to cultural and national ide.